Outcome at 1 year in patients with femoral shaft fractures treated with intramedullary nailing or skeletal traction in a low-income country: a prospective observational study of 187 patients in Malawi. (5th December 2020) - Chokotho, Linda; Wu, Hao-Hua; Shearer, David; Lau, Brian C; Mkandawire, Nyengo; Gjertsen, Jan-Erik; Hallan, Geir; Young, Sven
Abstract : Background and purpose — Intramedullary nailing (IMN) is underutilized in low-income countries (LICs) where skeletal traction (ST) remains the standard of care for femoral shaft fractures. This prospective study compared patient-reported quality of life and functional status after femoral shaft fractures treated with IMN or ST in Malawi. Patients and methods — Adult patients with femoral shaft fractures managed by IMN or ST were enrolled prospectively from 6 hospitals. Quality of life and functional status were assessed using EQ-5D-3L, and the Short Musculoskeletal Function Assessment (SMFA) respectively. Patients were followed up at 6 weeks, 3, 6, and 12 months post-injury. Results — Of 248 patients enrolled (85 IMN, 163 ST), 187 (75%) completed 1-year follow-up (55 IMN, 132 ST). 1 of 55 IMN cases had nonunion compared with 40 of 132 ST cases that failed treatment and converted to IMN (p < 0.001). Quality of life and SMFA Functional Index Scores were better for IMN than ST at 6 weeks, 3 and 6 months, but not at 1 year. At 6 months, 24 of 51 patients in the ST group had returned to work, compared with 26 of 37 in the IMN group (p = 0.02). Interpretation — Treatment with IMN improved early quality of life and function and allowed patients to return to work earlier compared with treatment with ST. Approximately one-third of patients treated with ST failed treatment and were converted to IMN.